Alcohol septal ablation as a modern and alternative treatment in patients with obstructive hypertrophic cardiomyopathy - Rudenko, K.; Nevmerzhytska, L.; Trembovetska, O.; Fanta, S.; Lazoryshynets, V. (Ukrainian Journal of Cardiovascular Surgery, 2016)
The results of 132 alcohol septal ablation procedures in patients with obstructive hypertrophic cardiomyopathy are presented. Short-term and long term results showed that the procedure of alcohol septal ablation could be an alternative treatment to surgery and dual chamber pacing if coronary anatomy is appropriate.